Diagnosis-to-Ablation Time and Recurrence of Atrial Fibrillation Following Catheter Ablation: A Systematic Review and Meta-Analysis of Observational Studies. (April 2020) - Chew, Derek S.; Black-Maier, Eric; Loring, Zak; Noseworthy, Peter A.; Packer, Douglas L.; Exner, Derek V.; Mark, Daniel B.; Piccini, Jonathan P.
Abstract : Background: The optimal timing of catheter ablation for atrial fibrillation (AF) in reference to the time of diagnosis is unknown. We sought to assess the impact of the duration between first diagnosis of AF and ablation, or diagnosis-to-ablation time (DAT), on AF recurrence following catheter ablation. Methods: We conducted a systematic electronic search for observational studies reporting the outcomes associated with catheter ablation for atrial fibrillation stratified by diagnosis-to-ablation time. The primary meta-analysis using a random effects model assessed AF recurrence stratified by DAT ⩽1 year versus >1 year. A secondary analysis assessed outcomes stratified by DAT ⩽3 years versus >3 years. Results: Of the 632 screened studies, 6 studies met inclusion criteria for a total of 4950 participants undergoing AF ablation for symptomatic AF. A shorter DAT ⩽1 year was associated with a lower relative risk of AF recurrence compared with DAT >1 year (relative risk, 0.73 [95% CI, 0.65–0.82]; P <0.001). Heterogeneity was moderate (I 2 =51%). When excluding the one study consisting of only patients with persistent AF, the heterogeneity improved substantially (I 2 =0%, Cochran's Q P =0.55) with a similar estimate of effect (relative risk, 0.78 [95% CI, 0.71–0.85]; P <0.001). Conclusions: Shorter duration between time of first AF diagnosis and AF ablation is associated with an increased likelihood of ablation procedural success. Additional study is required to confirm these results and to explore implementation of earlier catheter AF ablation and patient outcomes within the current AF care pathway. Abstract : Supplemental Digital Content is available in the text.